2022
DOI: 10.1101/2022.11.01.514783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MORC proteins regulate transcription factor binding by mediating chromatin compaction in active chromatin regions

Abstract: Background: The Microrchidia (MORC) proteins are a family of evolutionarily conserved GHKL-type ATPases involved in chromatin compaction and gene silencing. Arabidopsis MORC proteins act in the RNA-directed DNA methylation (RdDM) pathway, where they act as molecular tethers to ensure the efficient establishment of RdDM and de novo gene silencing. However, MORC proteins also have RdDM-independent functions; although, their underlying mechanisms are unknown. Results: In this study, we examined regions of MORC bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In this process, MORC likely forms dimers that topologically entrap DNA loops 42 and support chromatin condensation through synergistic covalent modification of nucleosomes catalyzed by its partner, the histone deacetylase HDAC3 1 . Our model was supported by a recent report showing how MORC proteins condense chromatin, reduce DNA accessibility to TFs, and thereby repress gene expression in the plant A. thaliana 43 . AP2XII-1 and AP2XI-2 co-depletion also drives hierarchical expression of secondary AP2s, all of which have restricted expression at pre-sexual stages and likely act as downstream activators or repressors during merogony.…”
Section: Discussionsupporting
confidence: 74%
“…In this process, MORC likely forms dimers that topologically entrap DNA loops 42 and support chromatin condensation through synergistic covalent modification of nucleosomes catalyzed by its partner, the histone deacetylase HDAC3 1 . Our model was supported by a recent report showing how MORC proteins condense chromatin, reduce DNA accessibility to TFs, and thereby repress gene expression in the plant A. thaliana 43 . AP2XII-1 and AP2XI-2 co-depletion also drives hierarchical expression of secondary AP2s, all of which have restricted expression at pre-sexual stages and likely act as downstream activators or repressors during merogony.…”
Section: Discussionsupporting
confidence: 74%
“…This is reminiscent of an earlier study reporting that MOM1 regulates transcription in intermediate heterochromatin, which is associated with both active and repressive histone marks 49 . Interestingly, the MOM1 complex and MORCs seem to behave similarly in binding active chromatin, as MORC7 was also reported to bind active chromatin devoid of RdDM 52 , and MORCs are colocalized at these MOM1 unique peaks. The mechanism of recruiting the MOM1 complex to these unique peaks and the function of MOM1 at these active chromatin sites is unknown.…”
Section: Discussionmentioning
confidence: 89%
“…It is possible that Pf MORC changes the nucleosome landscape by either direct association or by binding to different chromatin remodelers. Recent work in Arabidopsis has further confirmed the importance of At MORC paralogs in gene regulation by chromatin compaction (Zhong et al 2023), which resembles the function of Pf MORC in P. falciparum . Interestingly, in T. gondii , the major function of Tg MORC was in the repression of sex-determination genes (Farhat et al 2020), suggesting MORC family proteins have the capacity to perform diverse functions across eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 80%
“…Overall, since these seven ApiAP2 proteins are expressed at distinct time points during the P. falciparum cycle (Bozdech et al 2003) and regulate different sets of genes (Santos et al 2017, Josling et al 2020, Shang et al 2021, Shang et al 2022, Subudhi et al 2023), we believe this indicates a broad function of Pf MORC at different stages. In addition, a recent study reported that At MORC-mediated regulation of transcription may be due to both direct chromatin interactions or indirect association via sequence-specific transcription factors (Zhong et al 2023), suggesting a complex landscape of chromatin remodeling by MORC family proteins. We also interrogated the co-localization of Pf MORC and numerous epigenetic profiles (H2A.Z, H3K9ac, H3K4me3, H3K27ac, H3K18ac, H3K9me3, H3K36me2/3, H4K20me3, and H3K4me1), with a specific focus on H3K36me2, since it has been shown to act as a global repressive mark in P. falciparum (Karmodiya et al 2015) and other organisms (Strahl et al 2002, Wagner and Carpenter 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation